Dominion of God : Christendom and apocalypse in the Middle Ages - Whalen, Brett Edward (Harvard University Press, 2009)
Brett Whalen explores the compelling belief that Christendom would spread to every corner of the earth before the end of time. During the High Middle Ages - an era of crusade, mission, and European expansion - ;the Western followers of Rome imagined the future conversion of Jews, Muslims, pagans, and Eastern Christians into one fold of God's people, assembled under the authority of the Roman Church.